Analýza zpráv o fenoménu postižení v čínských dětských časopisech Analysis of Chinese children's newspaper reports on the phenomenon of disability - Hana Válková; Xingli Mu (Palacky University, 2007)
V této studii jsme zkoumali zprávy o postižení a postižených lidech v hlavních čínských dětských tiskovinách. Bylo vybráno osm časopisů z let 2003 až 2006, a to na základě těchto faktorů: celonárodní dosah, mediální pokrytí handicapů a postižených lidí, dostupnost (zdroje lze získat na internetu). Do této studie byly zahrnuty články, které se zabývaly specifickými handicapy, chronickými chorobami, jež vyvolávají invaliditu, nebo postižením jako takovým, a to v nadpisech, textu, na fotografiích nebo ilustracích. Celkem jsme zaznamenali 152 článků zaměřených na handicapy a postižené osoby. Poměr článků o postižení v čínském dětském tisku je 5,6 %, což je více než v České republice (2,3 %). Většina těchto článků byla zaměřena na děti, což bylo vyvoláno cílovou skupinou čtenářů. Obě studie prokázaly (v Číně i České republice) zvýšený počet článků z důvodu blížících se významných událostí. In this study we examined the reports on disability and people with disabilities in major Chinese children's newspapers. Eight newspapers from 2003 to 2006 were chosen on the basis of the following factors: national reach, media coverage of disabilities and people with disabilities, and availability (resources can be obtained through internet). Articles were selected for inclusion in this study if they referred to a specific disability, a chronic illness which incurs disabilities or to disability in general, whether in a headline, text, picture or illustration. There are 152 articles published related to disabilities and persons with disabilities in total. The proportion for report on disability is 5.6% in Chinese children's newspapers, which is higher than that (2.3%) in the Czech Republic. Most of the articles in this study were focused on children, which was determined by the target population of the newspapers. Both studies showed (in China and Czech Republic) an increased amount of reporting report due to greatly important events.